Emotional Support Animal Assessments: Toward a Standard and Comprehensive Model for Mental Health Professionals - Younggren, Jeffrey N. (Prof Psychol Res Pr, 2019)
Growth in the presence of Emotional Support Animals (ESAs) in our society has recently garnered a substantial amount of attention, both in the popular media and the professional literature. Public media abounds with stories focusing on the increasing number of animals claimed as ESAs, the impact of this growth on society, the industry claiming to certify ESAs, and the various types of animals described as “certified.” The authors propose an assessment model for ESAs certification comprising a four-pronged approach for conducting these types of assessments: (1) understanding, recognizing, and applying the laws regulating ESAs, (2) a thorough valid assessment of the individual requesting an ESA certification, (3) an assessment of the animal in question to ensure it actually performs the valid functions of an ESA, and (4) an assessment of the interaction between the animal and the individual to determine whether the animal’s presence has a demonstrably beneficial effect on that individual. This model aligns with professional ethics, standards of professional practice, and the law and seeks to provide clear guidelines for mental health professionals conducting ESA evaluations.